2017
DOI: 10.1002/andp.201700328
|View full text |Cite
|
Sign up to set email alerts
|

Generation of One‐Way Gaussian Steering by Gaussian Channel and Converting One‐Way Gaussian Steering by Beamsplitters

Abstract: Gaussian steering is used to characterize the intrinsic quantum correlation of Gaussian states under Gaussian measurement. Here we study the generation of one‐way Gaussian steering and the conversion of one‐way Gaussian steering. It is found that one‐way Gaussian steering could be generated by using Gaussian channels, either the Gaussian lossy channel or the Gaussian amplification channel. Exploiting the one‐way Gaussian steering in a two‐partite quantum system consists of two subsystems marked with A and B, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 52 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…Although one-way steering is observed from both  →  and  →  in various TMGSs ρ , [31,[33][34][35][36][37][38] we demonstrated that the state ρ can, in general , exhibit one-way steering solely from  → . Such unidirectionality restriction is shown to emerge as a consequence of the fact that the intensity difference of the modes  and  is verified to remain always positive, regardless of the physical and environmental parameters of ρ .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although one-way steering is observed from both  →  and  →  in various TMGSs ρ , [31,[33][34][35][36][37][38] we demonstrated that the state ρ can, in general , exhibit one-way steering solely from  → . Such unidirectionality restriction is shown to emerge as a consequence of the fact that the intensity difference of the modes  and  is verified to remain always positive, regardless of the physical and environmental parameters of ρ .…”
Section: Discussionmentioning
confidence: 99%
“…where   = 𝛽 − 𝛿 T 𝛼 −1 𝛿 represents the Schur complement of the mode  in the covariance matrix 𝜎  defined by Equation (35).…”
Section: Gaussian Quantum Steeringmentioning
confidence: 99%
See 3 more Smart Citations